MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR DENGAN MODEL COURSE REVIEW HORAY (CRH) DI SEKOLAH DASAR - Tri wiyoko; Aprizan Aprizan; Puji lasmono (Jurnal Muara Pendidikan, 2020)
This research is motivated by the low learning outcomes of fifth grade students in the field of science and the low learning activities of students. This study aims to improve the activity and student learning outcomes in class V SD 130 / II Pasir Putih Muara Bungo. The study was conducted in two cycles, each cycle consisting of planning, implementation, observation and reflection. Research subjects were 24 students. Data collection instruments consisted of observation sheets of student activities and essay questions. Data analysis techniques using qualitative descriptive analysis. The results showed an increase in student activity in the learning process in the first cycle an average of 79.98% and in the second cycle reached 90.77% with very good criteria. Furthermore students who complete their learning outcomes increased by 87.5% with very good criteria. So the application of the Course Review Horay (CRH) model can improve the activities and learning outcomes of science students in class V SD 130 / II Pasir Putih Muara Bungo.